Analyzing Trends in Blended Learning for Professional Growth: A Scopus Bibliometric Review - siti miati; Eveline Siregar; Cecep Kustandi (UIN Siber Syekh Nurjati Cirebon, 2023)
AbstractThis bibliometric review study investigates the current state of research on blended learning models for professional development based on articles indexed in the Scopus database. The study utilized various bibliometric methods to analyze publication trends, influential authors, institutions, journals, and keywords related to the topic. The search resulted in a total of 1,349 articles published from 2001 to March 2023, indicating a noticeable increase in publications in recent years. The analysis revealed that the United Kingdom is the leading country in research output, with Griffith University being the most productive institutions. The BMC Medical Education was identified as the top publishing outlet in the field. The study identified four keywords that represent the most commonly used terms in the literature: blended learning, online learning, assessment, and professional development. This study provides insights into the current research trends and gaps in the field of blended learning for professional development, which can inform future research directions and support the design of effective professional development programs.Keywords: bibliometric review, blended learning, professional development, Scopus database, research trends.Â AbstrakStudi tinjauan bibliometrik ini menyelidiki keadaan penelitian saat ini tentang model pembelajaran campuran untuk pengembangan profesional, berdasarkan artikel yang diindeks di database Scopus. Studi ini menggunakan berbagai metode bibliometrik untuk menganalisis tren publikasi, penulis berpengaruh, institusi, jurnal, dan kata kunci yang terkait dengan topik tersebut. Pencarian menghasilkan total 1.349 artikel yang diterbitkan dari tahun 2001 hingga Maret 2023, dengan peningkatan publikasi yang nyata dalam beberapa tahun terakhir. Analisis mengungkapkan bahwa Inggris adalah negara terdepan dalam hasil penelitian, dengan Universitas Griffith menjadi institusi paling produktif. BMC Medical Education diidentifikasi sebagai outlet penerbitan teratas di lapangan. Studi ini mengidentifikasi empat kata kunci yang mewakili istilah yang paling umum digunakan dalam literatur, termasuk pembelajaran campuran, pembelajaran online, penilaian, dan pengembangan profesional. Studi ini memberikan wawasan tentang tren dan kesenjangan penelitian saat ini di bidang pembelajaran campuran untuk pengembangan profesional, yang dapat menginformasikan arah penelitian di masa depan dan mendukung desain program pengembangan profesional yang efektif.Kata kunci: tinjauan bibliometrik, blended learning, pengembangan profesional, database Scopus, tren penelitian.